New evidence for the completeness of the Cleitophon from Plato’s musical symbolism - Kennedy, Jay (Classica - Revista Brasileira de Estudos Clássicos, 2010)
The evidence and arguments for a system of musical symbols in Plato’sdialogues presented in Kennedy’s 2011 The Musical Structure of Plato’s Dialoguesis here extended by showing that the Cleitophon has the same structure. Althoughthis short dialogue is often thought a mere fragment and incomplete, it is shown herethat it contains the complete musical structure and so is complete. This settles a longstanding, scholarly debate.